2000
DOI: 10.1002/(sici)1098-1004(200001)15:1<45::aid-humu10>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Human Gene Mutation Database?A biomedical information and research resource

Abstract: Although 20 years have elapsed since the first single basepair substitution underlying an inherited disease in humans was characterised at the DNA level, the initiative has only recently been taken to establish central database resources for pathological genetic variants. Disease-associated gene lesions are currently collected and publicised by the Human Gene Mutation Database (HGMD) in Cardiff, locus-specific mutation databases, and to some extent also by the Genome Database (GDB) and Online Mendelian Inherit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
121
0
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(126 citation statements)
references
References 9 publications
0
121
0
5
Order By: Relevance
“…Some SNPs have been proven to be very important and may be associated with human diseases. SNPs that lead to amino acid alteration in the protein are of particular interest because they are responsible for nearly half of the known genetic variations related to human inherited diseases (42). Researchers have found that some SNPs could change the response of an individual to certain drugs, susceptibility to environmental factors, such as microbial, and risk of developing particular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Some SNPs have been proven to be very important and may be associated with human diseases. SNPs that lead to amino acid alteration in the protein are of particular interest because they are responsible for nearly half of the known genetic variations related to human inherited diseases (42). Researchers have found that some SNPs could change the response of an individual to certain drugs, susceptibility to environmental factors, such as microbial, and risk of developing particular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…3). Indeed, F must approach zero (or nearly so) when we consider organisms that are increasingly close to humans, because suppressor (compensatory) substitutions rarely segregate in human populations, and most mutations causing Mendelian diseases are pathogenic unconditionally (26). Almost certainly, a mutation that is pathogenic to us was also pathogenic to Neanderthals.…”
Section: Discussionmentioning
confidence: 99%
“…All HGMD entries comprise a reference to the first literature report of a mutation, the associated disease state as specified in this report, the gene name, symbol and chromosomal location [11].…”
Section: Heterogeneous Association Rules Miningmentioning
confidence: 99%